2010
DOI: 10.1128/aac.01101-09
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Inhibits Hepatitis B Virus Replication in Transgenic Mice

Abstract: Pharmacological modulation of cellular proteins as a means to block virus replication has been proposed as an alternative antiviral strategy that may be less susceptible than others to the development of viral drug resistance. Recent evidence indicates that the ubiquitin-proteasome pathway interacts with different aspects of the hepatitis B virus (HBV) life cycle in cell culture models of virus replication. We therefore examined the effect of proteasome inhibition on HBV replication in vivo using HBV transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Therefore, proteasome activation seems to be a valuable strategy of the infected cells to reduce the stress resulting from misfolded proteins. In accordance to this, an inhibitory effect of proteasome inhibition by bortezomib on HBV replication can be observed in cell culture (see supplemental material) and in HBV transgenic mice (55).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Therefore, proteasome activation seems to be a valuable strategy of the infected cells to reduce the stress resulting from misfolded proteins. In accordance to this, an inhibitory effect of proteasome inhibition by bortezomib on HBV replication can be observed in cell culture (see supplemental material) and in HBV transgenic mice (55).…”
Section: Discussionmentioning
confidence: 51%
“…This might not be sufficient for a strong inhibition of the proteasomal activity based on a direct interaction of HBx with the proteasome (50). Moreover, recent data demonstrated that inhibition of the proteasomal activity impair HBV replication, arguing against an inhibitory effect of HBx on the proteasome (55). In addition, it was reported recently that HBx induces the degradation of insulin receptor substrate 1 via the ubiquitin-proteasome pathway (60).…”
Section: Discussionmentioning
confidence: 99%
“…E6AP is also associated with degradation of another tumor suppressor pRb by HCV NS5B protein [42]. The positive role of the UPS in virus replication was further demonstrated by proteasome inhibitors that interfere with the replication of several human pathogens such as herpesviruses [43,44], hepadnaviruses [45], and influenza viruses [46].…”
Section: Discussionmentioning
confidence: 96%
“…11 One report stated that BOR suppresses HBV proliferation in vitro. 12 Two reports described HBV reactivation in patients receiving BOR therapy for myeloma. One study described a patient treated with BOR as salvage therapy after ASCT, 7 and another study described an HBsAg-positive patient discontinuing lamivudine prophylaxis.…”
Section: Discussionmentioning
confidence: 99%